2004
DOI: 10.1177/1075547004270164
|View full text |Cite
|
Sign up to set email alerts
|

Clarity Across the Disciplines

Abstract: Computer-based readability measures were used to examine the clarity of texts written in the sciences, the social sciences, and the arts and humanities. Five studies examined texts that were written in these different disciplines for different audiences, moving from fellow researchers to students and the general public. Readability increased across these genres until it reached an asymptote. In several cases, the scientific texts used shorter sentences and were easier to read than were their parallel texts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…One common readability metric is the Flesch Reading Ease score (Flesch, 1948). Flesch found scientific journals to be "very difficult" to read, a finding that has been corroborated frequently and (Weeks & Wallace, 2002) and a geology journal (Hartley, Sotto, & Fox, 2004). Based on the Flesch score and other formulas, it is estimated that only about 5% of the US population can read and understand these medical journals.…”
Section: Evaluating Clarity In Science Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…One common readability metric is the Flesch Reading Ease score (Flesch, 1948). Flesch found scientific journals to be "very difficult" to read, a finding that has been corroborated frequently and (Weeks & Wallace, 2002) and a geology journal (Hartley, Sotto, & Fox, 2004). Based on the Flesch score and other formulas, it is estimated that only about 5% of the US population can read and understand these medical journals.…”
Section: Evaluating Clarity In Science Communicationmentioning
confidence: 99%
“…: (1) Short words that can be hard to understand (e.g., "average" vs. "mean"); (2) Short yet confusing sentences (e.g., "These parts store iron ions cells bind") (3) Non-textual features such as numbers and formulas, (4) The text's overall audience appeal, cultural appropriateness, tone, etc. ; and, most importantly for this study, (5) The reader's background knowledge of the topic being discussed, and in particular, the reader's familiarity with the vocabulary used (e.g., "Plants fix carbon") (Hartley et al, 2004;Stableford & Mettger, 2007).…”
Section: Evaluating Clarity In Science Communicationmentioning
confidence: 99%
“…1; for another example of this pattern, see Breeze 2016). The mean readability score for both text types in all journals was around 20-25, well below 50, the threshold proposed to delineate accessibility by nonspecialists (Hartley et al 2004;Kirkpatrick et al 2017). This low readability is not surprising, given that guidelines provided to authors for writing summaries do not emphasize characteristics that influence readability, such as sentence length or complexity (Supporting Information Table S1).…”
mentioning
confidence: 89%
“…For each journal we then analyzed the summaries and abstracts published in 2020 and 2021. We quantified readability using the Flesh Reading Ease (FRE) index which uses the length of words and sentences to calculate the ease of reading, with scores ranging from 0 to 100 with a score of 50 or greater recommended to enable access by nonspecialists (Hartley et al 2004; Kirkpatrick et al 2017). We also measured jargon by applying the De‐Jargonizer (Rakedzon et al 2017) which uses a corpus of over 90 million words and identifies “jargon” words rarely encountered by a nonsubject specialist, with a level of 2–5% unfamiliar jargon proposed to be required for accurate comprehension (Rakedzon et al 2017 and references therein).…”
Section: Are Summaries More Accessible Than Abstracts?mentioning
confidence: 99%
“…For example, a recent quantitative study found a higher number of hedge words (probably, possibly, etc .) in philosophy compared to other disciplines, and these words hinder comprehension (Hartley, Sotto, and Fox, 2004). An appropriate mood can help the reader grasp the main lines of an argument better.…”
Section: Why Mood Matters For Philosophizingmentioning
confidence: 99%